Multifocal Retroperitoneal Sarcoma - Theodosios Theodosopoulos; Dionysios Dellaportas; Vasiliki Psychogiou; Anneza Yiallourou; George Polymeneas; Georgios Gkiokas; Dionysios Voros (Case Reports in Surgery)
Introduction. Retroperitoneal sarcomas comprise a small proportion of all soft tissue sarcomas, and multiple factors influence their clinical behavior. Histopathological type and grade as well as complete surgical resection especially on the first operative attempt are well recognized as the main prognostic factors. Multifocality is another prognostic factor, which compromises therapy and finally makes prognosis worse due to multiple adverse implications. Case Presentation. A rare case of a 65-year-old male patient suffering from a multifocal retroperitoneal liposarcoma successfully treated in our hospital is presented herein. Discussion. Also, general considerations for these tumors are discussed, and especially multifocality is underlined as an ominous sign of retroperitoneal sarcomas behavior. Despite multifocality, once again complete surgical excision remains the mainstay of treatment of these patients, as long as further systemic and local therapies do not provide durable results.